Annual financial statements, the importance of other comprehensive income - Warzocha, Grzegorz (Roczne sprawozdanie finansowe, wpływ sprawozdania z pozostałych całkowitych dochodów, 2018)
The objective of the research was to verify whether the financial information presented in other comprehensive income has a material impact on the statement of total comprehensive income and financial statements viewed as a whole. The research focused primarily on the presentation requirements defined by the International Accounting Standard IAS 1 Presentation of Financial Statements and study of the annual reports filed in 2014-2016 by the WIG 20 constituent companies listed on the Warsaw Stock Exchange. In order to assess whether the impact of the financial information reported in other comprehensive income is material, relevant concepts of materiality were applied. It was tentatively assumed that the financial information presented in other comprehensive statement will be material. The results of the conducted research study confirmed in general this assumption
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 2, s. 90-101
Keywords: other comprehensive income; financial statements; financial reporting; pozostałe całkowite dochody; sprawozdanie finansowe; sprawozdawczość finansowa